An empirical model for forest landscape planning and its financial consequences for landowners. Issue 7 (17th November 2021) - Bostedt, Göran; de Jong, Johnny; Ekvall, Hans; Hof, Anouschka R.; Sjögren, Jörgen; Zabel, Astrid
ABSTRACT: Despite well-formulated goals for environmental protection in the forestry sector, the biodiversity crisis remains. Protected habitats are often small, isolated and lack continuity. We studied forest planning at a landscape scale as a method to increase habitat connectivity, and improve conservation values whilst maintaining high levels of forest production. We assessed the financial impacts of landscape planning for the landowners, and present a fee-fund system to solve unequal burdens among them. As case studies, we used three landscapes along a latitudinal gradient in Sweden. The results demonstrate some variation between the landscapes in terms of the total cost for set asides and large differences in terms of the financial impact per landowner. Our conclusion is that forest landscape planning may be a way forward to improve conservation efforts, but given the variation in financial impacts, we propose to combine landscape planning with economic tools for compensation.